A Stakeholder-Engaged Approach to Development of an Animal-Assisted Intervention for Obesity Prevention Among Youth With Autism Spectrum Disorder and Their Pet Dogs - Linder, Deborah E.; Folta, Sara C.; Must, Aviva; Mulé, Christina M.; Cash, Sean B.; Halbreich, Eli D.; Colón, Candice; Sullivan, Sandy; Sanabria, Edward; Gibbs, Debra; Farrell, Terri (Frontiers in Veterinary Science, 2021)
Stakeholder involvement in research has been demonstrated to increase the effectiveness, validity, and quality of a study. This paper describes the engagement of a stakeholder panel in the development and implementation of an animal-assisted intervention (AAI) assessment and program for children diagnosed with Autism Spectrum Disorder (ASD). Canines for Autism Activity and Nutrition (CAAN) aims to promote physical activity and wellness among children diagnosed with ASD by integrating activities with their pet dog during the child’s ongoing Applied Behavioral Analysis (ABA) in-home therapy sessions. Feedback from stakeholders guided program development at each stage of the research process, including this publication. Utilizing a stakeholder informed approach was essential for the development of assessment tools, program materials, and program design. Methods that may assist others to effectively partner with stakeholders to implement an AAI among children diagnosed with ASD or related disorders are described.